Change in the profiles lipid, digesta cholesterol and propionic acid of rats fed with of seaweed powder-based diets - Herpandi .; Made Astawan; Nurheni Sri Palupi (Jurnal Teknologi dan Industri Pangan, 2006)
Community’s consumption pattern with high fat-low fiber has caused the prevalence of degenerative disease, i.e.cardivascular disease. Coronary Heart Disease (CHD) is the first cause of death in Indonesia. Seaweed is a fiber rich food and has a hypocholesterolemic effect. Objectives of the research were to investigate the changes of lipid profiles, digesta cholesterol and propionic acid of rats fed with seaweed powder-based diet. Five groups of six male Sprague Dawley hypercolesterolemia rats were feed by 0% cholesterol and 0% seaweed powder (negative control); 1% cholesterol and 10% Eucheuma cottonii, 1% cholesterol and 10% Gelidium sp,1% cholesterol and 10% Sargassum sp, and 1% cholesterol and 0% seaweed powder (positive control) for 31 days. The experiment result showed that the seaweed powder did not have a significant effect (P>0,05) on the growth and feed consumption, and serum HDL (Hight Density Lipoprotein) but has a significant effect (P